2013
DOI: 10.7763/ijtef.2012.v3.249
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Saving Attitude: Does Parents’ BackgroundMatter?

Abstract: Abstract-Parents play important roles in educating their child to behave appropriately in all aspects of life including financial management. The aim of this paper is to identify the influence of parents' background on savings attitude among students in a Malaysian local university. The findings of the research provide useful information to parents as well as public on the importance of early financial planning exposure toward teenagers, in encouraging savings habit. 2146 questionnaires were distributed among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
(2 reference statements)
2
6
0
1
Order By: Relevance
“…Young people also learnt from direct and indirect interaction with peers; through discussions, rulemaking, reinforcement and modeling. Salikin, Wahab, Zakaria, Masruki and Nordin (2012) found that parental educational background and household income affects the saving tendency of students. Mother's level of education affected the tendency to save for students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young people also learnt from direct and indirect interaction with peers; through discussions, rulemaking, reinforcement and modeling. Salikin, Wahab, Zakaria, Masruki and Nordin (2012) found that parental educational background and household income affects the saving tendency of students. Mother's level of education affected the tendency to save for students.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents had more savings accounts and live in households where head of household was married, had more education and owned assets. Salikin et al (2012) revealed that parents' education background affects respective percentage and purposes of savings. If parents have higher level of educational background then students separate lower amount for savings.…”
mentioning
confidence: 99%
“…Also, males were found to have higher levels of financial awareness compared to females (HSR, 1993). On the other hand, Salikin et al (2012) found that higher level of parents' education background and higher household income did not contribute for students in fund savings. Mu'at, Julina and Triandani (2015) found no differences between gender on financial literacy.…”
Section: Literature Reviewmentioning
confidence: 85%
“…The "simply to have money put aside" motive could have an underlying influence of parental background. Salikin et al (2012) submitted that education and level of household income have a negative correlation with the likelihood to save. In other words, the poorer the parents, the higher the likelihood of the offspring saving.…”
Section: Test Of Ho1 : Farmer's Attitude Towards Saving Is Not Above Averagementioning
confidence: 99%